Waste to worth: bioplastic synthesis from lignocellulosic food waste in the age of the circular bioeconomy - Vatieri, Chiara; Cirillo, Teresa; Esposito, Francesco (Frontiers in Sustainable Food Systems, 2025)
The amount of agroindustrial waste, often rich in lignocellulosic components, has increased in recent years due to population growth and the resulting increase in food consumption. Improper disposal of food waste at the end of its life significantly impacts the environment by emitting greenhouse gases into the atmosphere. For this reason, Europe is mobilizing through the implementation of legislation that applies the circular economy model to the recovery of lignocellulosic rich food waste and its conversion into value-added products, such as bioplastics. Bioplastics have also been among the most discussed topics recently, as they could be an excellent alternative to conventional plastics. Therefore, companies have recently set out to give food waste a second life by converting it into bioplastics derived from cellulose and other lignocellulosic fractions. As far as the environmental impact is concerned, recycling seems to be the best way to handle food waste, as it fits into the concept of a circular bioeconomy leveraging lignocellulosic feedstocks and reducing greenhouse gas emissions. It is also important to compare European and non-European regulations on the application of the circular economy model. This review aims to categorize food waste and lignocellulosic biomass, identify related issues, and explore how it can be reused as a resource for producing value added products such as bioplastics. It also explores the potential of recycling as a means of reducing pollution from plastic and food waste. Finally, the concept of ecological sustainability and the application of circular economy models are examined.